2012
DOI: 10.1038/ncomms1667
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ contributes to PKM2 and HK2 expression in fatty liver

Abstract: Rapidly proliferating cells promote glycolysis in aerobic conditions, to increase growth rate. Expression of specific glycolytic enzymes, namely pyruvate kinase M2 and hexokinase 2, concurs to this metabolic adaptation, as their kinetics and intracellular localization favour biosynthetic processes required for cell proliferation. Intracellular factors regulating their selective expression remain largely unknown. Here we show that the peroxisome proliferator-activated receptor gamma transcription factor and nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
108
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 46 publications
11
108
0
2
Order By: Relevance
“…We demonstrated that Slu7 downregulation resulted in significantly increased hepatic glucose uptake and catabolism, as demonstrated by intrahepatic lactate concentrations ( Figure 6, B-D). The forced expression of PKM2 and HK2 activates hepatocellular growth in normal liver (39). We found that the cell cycle-related genes Foxm1, Nor1, and early growth response 1 (Egr1) and the cyclins Ccnd1, Ccna2, and Ccnb2 were all upregulated in Slu7-depleted mouse livers and in SLU7-silenced HepG2 cells ( Figure 7A and Supplemental Figure 6).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…We demonstrated that Slu7 downregulation resulted in significantly increased hepatic glucose uptake and catabolism, as demonstrated by intrahepatic lactate concentrations ( Figure 6, B-D). The forced expression of PKM2 and HK2 activates hepatocellular growth in normal liver (39). We found that the cell cycle-related genes Foxm1, Nor1, and early growth response 1 (Egr1) and the cyclins Ccnd1, Ccna2, and Ccnb2 were all upregulated in Slu7-depleted mouse livers and in SLU7-silenced HepG2 cells ( Figure 7A and Supplemental Figure 6).…”
Section: Resultsmentioning
confidence: 74%
“…Slu7 knockdown resulted in downregulation of Mat1a, glutaminase 2 (Gls2), glucokinase (Gck), and L-pyruvate kinase (Lpk) and concomitant upregulation of Mat2a, Gls1, hexokinase 2 (Hk2), and pyruvate kinase m2 (Pkm2), together with a switch in the expression of Hnf4α isoforms derived from the P1 and P2 gene promoters and in the ratio of Insr A and B splice variants ( Figure 3E and Supplemental Figure 2). The isozymes, Hnf4α P2-derived isoforms, and splice variants favored upon Slu7 downregulation were characteristic of the fetal and/or transformed hepatocyte, which exert profound effects on metabolism (26,30,(36)(37)(38)(39)(40).…”
Section: Resultsmentioning
confidence: 99%
“…We first evaluated the nuclear ploidy profile in 3-month-old Pten KO mice at pretumoral stages. At this age, the Pten KO mouse liver shows extensive steatohepatitis (51,52). Similar to other NAFLD models, the ploidy profile of Pten KO livers was different from that of WT livers and was characterized by the amplification of the highly polyploid mononuclear population (Supplemental Figure 2A and Table 2).…”
Section: Introductionmentioning
confidence: 67%
“…Lanes were run on the same gel but were noncontiguous. (52). For investigations with the antioxidant NAC, heterozygous male and female ob/+ mice were mated and had a free access to water with or without 10 mM NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation